2001
DOI: 10.1029/2000jc000337
|View full text |Cite
|
Sign up to set email alerts
|

Wave‐formed sand ripples at Duck, North Carolina

Abstract: Abstract. A recently developed acoustic multiple transducer array was utilized to measure small-scale bed forms in the nearshore and inner shelf regions at Duck, North Carolina. Two populations of wave-formed ripples were observed: short wave ripples (SWR) with heights ranging from 3 mm to 2 cm and lengths ranging from 4 to 25 cm and long wave ripples (LWR) with heights ranging from 3 mm to 6 cm and lengths ranging from 35 to 200 cm. The SWR were only present sometimes, and their presence or absence was determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
99
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(112 citation statements)
references
References 25 publications
(16 reference statements)
12
99
0
1
Order By: Relevance
“…Recently, Hanes et al (2001) observed in the field long-wave ripples (LWR) with relatively small heights (ranging from 3 mm to 6 cm) and large lengths (ranging from 35 to 200 cm). LWR were observed to be not as dynamics as the small-wave ripples (SWR) commonly observed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hanes et al (2001) observed in the field long-wave ripples (LWR) with relatively small heights (ranging from 3 mm to 6 cm) and large lengths (ranging from 35 to 200 cm). LWR were observed to be not as dynamics as the small-wave ripples (SWR) commonly observed.…”
Section: Introductionmentioning
confidence: 99%
“…Combined flows are difficult to produce in the laboratory, and the bed forms produced by combined flows include both 2D ripples and a variety of three-dimensional (3D) bed forms, posing a more complex predictive problem than pure wave-generated ripples. Field studies of bed forms produced by waves and currents include those by Amos et al [1988]; Li and Amos [1998]; Osborne and Vincent [1993]; Traykovski et al [1999]; Hanes et al [2001]; Smyth and Li [2005].…”
Section: Introductionmentioning
confidence: 99%
“…CHANG AND HANES: MILDLY SLOPED LONG WAVE RIPPLES seabed exhibited LWR that are typical of the location [Hanes et al, 2001]. In these two data sets, however, the ABS was at relatively different locations on the ripple profile.…”
Section: C07022mentioning
confidence: 94%
“…Rather, they are parameterized by the hydraulic roughness. In order to examine the effects of bed roughness more effectively, we superimposed 20 SWR [Hanes et al, 2001] upon the LWR in the computational domain. The size of each SWR is 10 cm in length and 0.5 cm in height.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation